A Comparison between the Level of Interleukin 10 (IL-10) in Aterm and Preterm Labor - Lisangan, Yusri (Indonesian Socety of Obstetrics and Gynecology, 2012)
Objective: To compare the level of interleukin 10 in aterm and preterm labor. Method: The research was conducted from November 1st 2011 until January 31st 2012. The subjects were pregnant women underwent labor during the period who had agreed to participate in this study. The study was conducted in the Obstetrics and Gynecology departments of several teaching hospitals of Hasanuddin University in Makassar. The study design was cross sectional with 48 samples. The data were analysed by using the Mann Whithney test. Results: The result revealed that there was an increase of interleukin 10 level in mothers with preterm labor, in comparison with the control group (p < 0.05). Conclusion: The level of interleukin 10 in mothers with preterm labor are higher than aterm labors less than espective. [Indones J Obstet Gynecol 2012; 36-4: 163-6] Keywords: interleukin 10, preterm labor